2019
DOI: 10.1128/iai.00884-18
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Selection for Pathogenicity Mutations in Staphylococcus aureus Identifies Novel Factors Relevant to Chronic Infection

Abstract: Adaptation of Staphylococcus aureus to host microenvironments during chronic infection involves spontaneous mutations, yet changes underlying adaptive phenotypes remain incompletely explored. Here, we employed artificial selection and whole-genome sequencing to better characterize spontaneous chromosomal mutations that alter two pathogenicity phenotypes relevant to chronic infection in S. aureus: intracellular invasiveness and intracellular cytotoxicity. We identified 23 genes whose alteration coincided with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…These differences between mutant 1801_2010, WT Newman_2010, and Newman_WT strains in Figure 1 indicate these genetic changes are potentially responsible for phenotypic variation. However, a phenotypic trait caused by genetic sources of variation could include additive variance, dominant variance, environmental variance (e.g., organismal adaptation), and epistatic variance [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These differences between mutant 1801_2010, WT Newman_2010, and Newman_WT strains in Figure 1 indicate these genetic changes are potentially responsible for phenotypic variation. However, a phenotypic trait caused by genetic sources of variation could include additive variance, dominant variance, environmental variance (e.g., organismal adaptation), and epistatic variance [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…LTA biosynthesis is a highly conserved function in Gram-positive organisms. Point mutations causing amino acid variants can possibly alter protein production, protein-protein interactions, protein structure, and/or protein function ( McLean et al, 2019 ). Previous studies have similarly identified genetic differences in LTA biosynthesis leading to structural changes in Streptococcus suis strains, which may have implications for influencing the host immune response, though this has not been extensively studied in S. aureus clinical strains ( Gisch et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aggravating the analysis of clinical SCVs so far, indubitable identification of genes causative for the phenotype switch is only possible for stable SCVs that already underwent mutational adaption and by comparison with a revertant phenotype that spontaneously emerged from the SCV phenotype (Becker et al, 2006; Schleimer et al, 2018). Besides the rarely isolated stable clinical SCVs, in vitro selection for stable SCVs mandatory for WGS as well as for transcriptomics and proteomics can be performed by cultivation in the presence of sublethal concentrations of certain antibiotics (e.g., aminoglycosides) (Balwit et al, 1994) or by serially passaging bacteria in the presence of HeLa cells using modified gentamicin protection assays (McLean et al, 2019). By using these methods, however, the SCV-selective mutations only occur in the corresponding drug target genes or genes essential for antibiotic uptake (Schaaff et al, 2003; McLean et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the rarely isolated stable clinical SCVs, in vitro selection for stable SCVs mandatory for WGS as well as for transcriptomics and proteomics can be performed by cultivation in the presence of sublethal concentrations of certain antibiotics (e.g., aminoglycosides) (Balwit et al, 1994) or by serially passaging bacteria in the presence of HeLa cells using modified gentamicin protection assays (McLean et al, 2019). By using these methods, however, the SCV-selective mutations only occur in the corresponding drug target genes or genes essential for antibiotic uptake (Schaaff et al, 2003; McLean et al, 2019). Further approaches selecting for a stable SCV phenotype include a chemostat to generate steady-state growth conditions with low nutrients and low growth rate for a prolonged time and with specific chemical stress (Bui and Kidd, 2015; Bui et al, 2015).…”
Section: Introductionmentioning
confidence: 99%